Life and energy - Asimov, Isaac (A discus book, 1962)
Life and energy is a brilliant introduction to the chemistry of life. In this highly lucid guide to the dynamics of modern biology, Isaac Asimov deftly explores the most recent discoveries in this constantly surprising field of inquiry. In the first part, he explains the mechanics of the inanimate world, the significance of energy, work, motion, heat, and chemical reaction. He then uses these concepts in the second half to analyze and explain the latest advances in the study of enzymes, amino acids, proteins and the very processes which constitute life itself. In short, Dr. Asimov's keen examination of biology's current desire to isolate and control the very basis of life--the significance of which promises to revolutionize life itself--becomes a fascinating as well as informative excursion. Illustrated with drawings, charts and diagrams.